2008
DOI: 10.1007/s10751-008-9855-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of iron meteorite Sikhote–Alin and extracted iron–nickel phosphides using Mössbauer spectroscopy with high velocity resolution

Abstract: Comparative study of schreibersite and rhabdite extracted from SikhoteAlin (IIAB) iron meteorite using Mössbauer spectroscopy, X-ray diffraction and magnetic measurements was carried out. Mössbauer spectra of bulk meteorite sample and extracted phosphides were recorded in 4,096 channels and then presented in 1,024 channels. Differences of the unit cell structure, the Fe, Ni and Co content, the room temperature Mössbauer spectra and Curie temperature for rhabdite and schreibersite were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Mössbauer spectroscopy (Figure 16) shows that the main element, Fe (39%), is only related to the abundance of maghemite and troilite. The RT spectrum is similar to that obtained for schreibersite pieces of Sikhote-Alin iron meteorite [40][41][42][43] but, in fact, in our case it shows superparamagnetic behavior with iron in trivalent coordination, as indicated in Table 5, and splits at 4.2 K. Most of the 4.2 K spectrum was fitted with the two sextets of maghemite expected at this temperature (see for instance [44]), plus a very small amount (1.1%) of troilite (FeS). Troilite was fitted with only one sextet, as explained in other works [45], instead of an octet.…”
Section: Stony Meteoritesupporting
confidence: 76%
“…Mössbauer spectroscopy (Figure 16) shows that the main element, Fe (39%), is only related to the abundance of maghemite and troilite. The RT spectrum is similar to that obtained for schreibersite pieces of Sikhote-Alin iron meteorite [40][41][42][43] but, in fact, in our case it shows superparamagnetic behavior with iron in trivalent coordination, as indicated in Table 5, and splits at 4.2 K. Most of the 4.2 K spectrum was fitted with the two sextets of maghemite expected at this temperature (see for instance [44]), plus a very small amount (1.1%) of troilite (FeS). Troilite was fitted with only one sextet, as explained in other works [45], instead of an octet.…”
Section: Stony Meteoritesupporting
confidence: 76%
“…4. The room temperature spectrum of rhabdite microcrystals demonstrated superparamagnetic behavior (earlier we evaluated the Curie temperature for rhabdite by magnetization measurements of about 345 K [9]). It was better fitted using three magnetic sextets and one paramagnetic doublet.…”
Section: Resultsmentioning
confidence: 99%
“…Recently Mössbauer spectroscopy with a high velocity resolution demonstrated new possibilities in the study of various iron bearing phases in meteorites [4][5][6][7][8]. Our previous study of iron nickel phosphides demonstrated superparamagnetic Mössbauer spectrum of rhabdite at room temperature [9]. In this work we present new preliminary results of the study of iron nickel phosphide microcrystals extracted from Sikhote-Alin iron meteorite using Mössbauer…”
Section: Introductionmentioning
confidence: 90%
“…These phases were identified based on well‐known properties such as isomer shift, hyperfine splitting, and quadrupole splitting used previously by Oshtrakh et al. () and Dos Santos et al. ().…”
Section: Experimental Methodsmentioning
confidence: 99%